Germanium thin films: a high-performance resistive anode for micro-pattern gaseous detectors - Wang, Xu; Zhang, Zhiyong; Wen, Sicheng; Liu, Jianbei; Shao, Ming; Zhou, Yi (Frontiers in Detector Science and Technology, 2026)
Resistive electrodes are a critical component of Micro-Pattern Gaseous Detectors (MPGDs) for dealing with discharges. This study introduces an advanced approach using germanium (Ge) thin films as resistive anodes in MPGDs. The Ge films are fabricated via vacuum thermal evaporation, which enables the production of large-area and uniform on rigid substrates. Characterization confirms the film stability for over 700 days, which is attributed to surface passivation. It also reveals an inverse correlation between resistivity and temperature. Micromegas detectors equipped with Ge resistive anodes achieve high gain, low spark rate and high rate capability. These results validate Ge-film resistive anodes as a reliable and scalable technology for improving the performance and stability of MPGDs in future particle physics experiments.